LEGAL PROTECTION SYSTEM FOR EQUITABLE REMUNERATION - Abduh, Rachmad (Proceeding International Seminar of Islamic Studies, 2023)
Employment is all matters relating to the workforce at the time before, during and after the work period. The phenomenon experienced by workers is that the wages they receive are not commensurate with the cost of living, the high cost of living makes workers far from prosperous. In addition to meeting basic needs, such as clothing, food and boards, workers must also bear the cost of education for their children and must also set aside a portion of their wages to be used when workers are unable to work anymore. According to Idan Hanifah, "from a wage point of view, it is distinguished from nominal wages, namely money and real wages, namely the number of goods that can be purchased with money.Islamic religious teachings highly respect agreements that are in accordance with provisions or syara' and include work agreements between workers and employers which contain the rights and obligations of each. And Islam obliges to comply with what is born of it from the provisions of the law. Labor law is a law that regulates labor, which was originally known as labor law. One of the functions of this regulation is to make it a means of renewal in the context of development, which can be interpreted as channeling human activities that lead to development.